Understanding emotional influences on sustained attention: a study using virtual reality and neurophysiological monitoring - Shen, Yang; Zheng, Huijia; Li, Yu; Tian, Xuetao (Frontiers in Human Neuroscience, 2024)
Emotion and attention regulation significantly influence various aspects of human functioning and behavior. However, the interaction between emotion and attention in affecting performance remains underexplored. This study zooms in sustained attention, one aspect of attention relevant to task performance, i.e., persistent attention and control during the task, and investigates how individual differences in sustained attention, in response to emotional state variations, impact task performance. A total of 12 participants underwent emotion induction through Virtual Reality (VR) videos; completed an AX-CPT (continuous performance test) task to measure sustained attention, for which task performance is evaluated from two aspects, task accuracy and task reaction times; and reported their flow states. EEG and PPG data were collected throughout the sessions, as supporting evidence for sustained attention. Our findings suggest that emotional valence and arousal significantly influence task reaction times and sustained attention, when gender differences are accounted for, but do not significantly impact task accuracy. Specifically, males responded faster under high-arousal negative emotions, while females responded faster under high-arousal positive emotions. Additionally, we find that flow experience is not significantly impacted by emotions states or sustained attention. These results underscore the nuanced interplay between emotion, sustained attention, and task performance, and validate the use of VR, EEG, and PPG technologies in future research on related topics.